VIII International monotype festival “Watch and see” in the context of the issue of artistic perception and creative development of the artist (Journal of Philosophy Culture and Political Science, 2020)
The article analyzes the work of the VIII International Festival of Monotype “Watch and See” hostedin St. Petersburg in September 2019. The article object is consideration of monotypes that were presentedin exposition of the show, as well as learning the process innovation in print works during providedmaster classes. The modern approach to solving creative problems, monotype technologies and executiontechniques brings out in the article in considering the exhibited pieces of works. The practical significancein the scientific article is in consideration of modern approaches to solving the figurative conceptof the work in the technique of monotype. New knowledge was received based on conducted researchmethods ‒ visual, comparative analysis method, iconological and iconographic analysis. Graphics artistsoften discover new artistic images during the process of working on monotype. Spontaneous compositionsof monotype influence on the unexpected perception of different genres of this type of graphic.Creative imagination of artists is progressing as a result of the work process. The article shows interrelationbetween monotype as activation technique for creative thinking of the artist and the perception ofthe viewer. It is possible in the future that conclusions of the article to be used in the methodology ofgraphics studying and find practical application for issue solving of composition of drawing and painting.Key words: monotype technique, artistic image, intuition, associative thinking, improvisation,fantasy.